EKSISTENSI SENI HIAS RUMAH TRADISIONAL KUDUS - Arif Suharson; Dharsono Dharsono; Bambang Sunarto; Nanik Sri Prihatin (Institut Seni Indonesia Yogyakarta, 2021)
This study aims to understand the existence of Kudus traditional house decorative art that is formed in conjunction with the culture that enters the cultural life of the Kudus people. The presence of decorative art has an important meaning for the community because it is closely related to the noble values that become a learning vehicle for the next generation. Decorative art in Kudus traditional house made with a variety of decorative diversity that is behind it is a form of strong cultural perspective. The decorative art is deliberately made to have beautiful forms of stilisasi, magnificent but also related to the meaning of symbols. Grounded research with three steps of activity simultaneously, namely: data reduction, data presentation, and verification or withdrawal of conclusions with inter-pretative model analysis conducted to produce valid research. As a result of human culture, the phenomenon of artifacts is certainly inseparable from the sociocultural context in art. The decorative art of Kudus traditional house characterized by coastal culture was born with the strengthening of socio-economic progress of the community with the concept of